Antigone 'Resurrected': The Appropriation of Sophocles's Heroine in Interwar France. (3rd April 2017) - Read, Philippa
Abstract : This article argues the potency and ambivalence of Sophocles's heroine Antigone, as 'resurrected' in public and private debates in France immediately after the First World War. It shows that her myth was most significantly evoked in a polemic concerning not only the burial of the war dead, but also the responsibilities and individualism of those left behind to mourn. Existing analyses of women's wartime roles in France have tended to emphasize 'new' models of heroism or exemplary conduct created by ideological agendas in the exceptional circumstances of modern war. However, this article explores a less popularly analysed concept, that being the ways in which a traditionally and previous re-interpreted heroic female icon, Antigone, was appropriated after the war as a 'mouthpiece' for grieving women's lived experience. It sheds light on a significant gap in the scholarship of classical receptions in wartime France, providing a fuller and more contextualized discussion of interwar evocations of Antigone. It also considers the complexities associated with the study of an ancient subject 'transplanted' into modern contexts.